Cork suberin as a new source of chemicals.: 1. isolation and chemical characterization of its composition - Cordeiro, N. (2021)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1 H- and 13C-NMR, gas chromatogra phy coupled with mass spectrometric (GC–MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be v-hydroxymonocarboxylates, a,v-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.